A framework of consumer participation in the energy management of a smart community. (1st January 2014) - Wang, Ti; Yamashita, Daiki; Yokoyama, Ryuichi; Niimura, Takahide; Takamori, Hiroshi
This study aims at modelling a dynamic price-based management of the electrical energy needs of a community. A smart community we envision operates a portfolio of power generating facilities including renewable sources. A challenge is how to meet volatile and fluctuating demands via the dynamic pricing. We design a framework to implement the principle: 'Let the consumer be part of the optimiser'. We attempt to capture consumers' responsiveness to the price reflecting the tightness of demand and supply balance. An example here of the model community demonstrates that the dynamic pricing via a complementarity-based modelling approach invites consumers to respond and participate in enhancing efficiency in line with their own preferences.